Effect of BKCa Channel Opener LDD175 on Erectile Function in an In Vivo Diabetic Rat Model. Issue 1 (15th December 2016) - Sung, Hyun Hwan; Kang, Su Jeong; Chae, Mee Ree; Kim, Hye Kyung; Park, Jong Kwan; Kim, Chul Young; Lee, Sung Won
Abstract: Introduction: The development of novel therapeutic options is imperative in patients with erectile dysfunction, especially those non-responsive to phosphodiesterase type 5 inhibitors. LDD175, a potent BKCa channel opener, has a relaxation effect on the in vitro cavernosal smooth muscle strip. Aim: To investigate the effect of LDD175 on erectile function using in vivo animal disease model. Methods: Male Sprague-Dawley rats were assigned to a normal control group and seven diabetic groups: diabetic control, sildenafil (1 and 5 mg/kg), LDD175 (5 and 10 mg/kg), LDD175 5 mg/kg plus sildenafil 1 mg/kg, and LDD175 10 mg/kg plus tetraethylammonium. Main Outcome Measures: Intracavernosal pressure (ICP), ratio of ICP to mean arterial pressure (MAP), and the area under curve of ICP/MAP of eight groups were compared using in vivo pelvic nerve stimulation. Results: The ICP, ICP/MAP ratio, and area under curve of the ICP/MAP ratio of the normal control rats increased with an increase in electrical field stimulation voltage. All parameters in the diabetic control group were significantly lower than those in the normal control rats, with an electrical field stimulation ranging from 1 to 5 V ( P < .05). LDD175 improved the erectile response in diabetic rats in a dose-dependent manner. The combination of sildenafil (1 mg/kg) and LDD175 (5 mg/kg) showed a significant additive effect ( P < .05) on the improvement of erectile function compared with sildenafil (1 mg/kg) alone. The enhancement of erectile function by LDD175 was completely blocked by tetraethylammonium. Conclusion: The results showed that the BKCa channel opener LDD175 improved erectile function in an in vivo diabetic rat model. Furthermore, combination therapy of LDD175 and sildenafil had an additive effect on the improvement of erectile function in diabetic rats. LDD175 could be a new candidate for the treatment of erectile dysfunction.